2016
DOI: 10.7567/jjap.56.01af03
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric-pressure plasma activation and surface characterization on polyethylene membrane separator

Abstract: The surface hydrophilic activation of a polyethylene membrane separator was achieved using an atmospheric-pressure plasma jet. The surface of the atmospheric-pressure-plasma-treated membrane separator was found to be highly hydrophilic realized by adjusting the plasma power input. The variations in membrane separator chemical structure were confirmed by Fourier transform infrared spectroscopy and X-ray photoelectron spectroscopy. Chemical analysis showed newly formed carbonyl-containing groups and high surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Figure shows the ATR‐FTIR spectra of cyclonic plasma deposited 316 stainless steel samples compared with undeposited 316 stainless steels. The main features of the ATR‐FTIR spectra include two chemical groups: a peak in the region of 801 to 845 cm −1 corresponding to SiRx (R represents methyl group) and a peak in the region of 980 to 1230 cm −1 corresponding to Si–O–Si. From ATR‐FTIR analysis, the noticeable organic silicon feature such as Si–O–Si and SiCH 3 dominate the atmospheric pressure plasma deposited 316 stainless steels.…”
Section: Resultsmentioning
confidence: 99%
“…Figure shows the ATR‐FTIR spectra of cyclonic plasma deposited 316 stainless steel samples compared with undeposited 316 stainless steels. The main features of the ATR‐FTIR spectra include two chemical groups: a peak in the region of 801 to 845 cm −1 corresponding to SiRx (R represents methyl group) and a peak in the region of 980 to 1230 cm −1 corresponding to Si–O–Si. From ATR‐FTIR analysis, the noticeable organic silicon feature such as Si–O–Si and SiCH 3 dominate the atmospheric pressure plasma deposited 316 stainless steels.…”
Section: Resultsmentioning
confidence: 99%
“…This shows that the electrolyte solution is more stable in the plasma-treated separator than in the untreated separator. 28,29) Figure 8 shows the results of the charge-discharge characterization of Li-ion batteries using the plasma-treated and untreated PE separators. Charge and discharge tests were conducted between 2.0 and 4.0 V at 0.1 C rates.…”
Section: Resultsmentioning
confidence: 99%
“…In a demonstration of the advantages of atmosphericpressure plasma, Tseng et al have shown that the hydrophilicity of the separator can be tailored by controlling the plasma power input during the surface activation. [109] Qin et al used a reactive atmospheric pressure plasma in a binder-free, roll-to-roll configuration to coat PE separators with a SiO x C y H z nanoparticulate film. [110] The schematic is shown in Figure 35.…”
Section: Plasma Processes For Separatorsmentioning
confidence: 99%